Experimental study on static characteristics of the Yellow River silt under (triaxial) consolidated undrained conditions. Issue 3 (4th March 2023) - Wang, Yuke; Cao, Tiancai; Shao, Jinggan; Song, Yingbin; Wan, Yongshuai
Abstract: The siltation of reservoirs and rivers in the Yellow River Basin and the occurrence of flood disasters are mainly caused by silt transportation. The Yellow River silt being applied to practical production will help solve the problem of siltation in the Yellow River. In this paper, the consolidated undrained (CU) test of the Yellow River silt is carried out by using GDS triaxial apparatus. The effects of confining pressure, relative density and loading rate on the stress-strain relationship, strength parameters, generalized shear stress ratio and pore water pressure variation of the Yellow River silt are explored. The results show that, under the same axial strain, the deviator stress increases with the increase of confining pressure and relative density, and decreases with the increase of loading rate; compared with the relative density, the effect of the confining pressure and loading rate on the generalized shear stress ratio is insignificant. The friction angle is affected by relative density and confining pressure in varying degrees, but less by loading rate. The secant modulus and initial tangent modulus increase with the increase of confining pressure and relative density. The pore water pressure first increases to the positive peak value, and then decreases to a negative value gradually with the increase of axial strain under most conditions. The pore water pressure variation is affected by the confining pressure and relative density obviously, while affected by the loading rate insignificantly.